Limit versus full creep-feeding of a high protein supplement to calves grazing late summer bluestem - Cochran, R.C.; Binns, C.E.; Corah, L.R.; DelCurto, T.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Limit creep-feeding a 36% protein supplement (avg. salt concentration = 7.9%) was compared with unlimited consumption of the same supplement without salt (full creep-feeding) and with no supplementation. Average daily gain of steer calves was increased (P≤.06) by.19 (limit creep-feeding) and .38 (full creep-feeding) lb per day compared with non-supplemented calves. Average daily gain of heifer calves was not increased by creep feeding. Efficiency with which creep was converted to extra gain was poor for both limit and full creep-feeding groups. Little difference was observed in postweaning average daily gains; however, the calves given ad libitum access to creep feed tended (P=.12) to have greater daily gains (1.9 lbs) than non creep-feeding calves (1.6 lbs). Limit creep-fed calves had average daily gains of 1.7 lbs. Feed conversion during the post-weaning period was slightly improved (P=.09) in calves that had been given ad libitum access to creep feed.
Keywords: Beef; Limit vs. full creep-feeding; Bluesteam; Protein; Calves